Risk Factors of HIV and AIDS Mortality At Ibnu Sina Hospital - Silvanus Roga Misi; Chatarina Umbul Wahyuni; Hari Basuki Notobroto (Humanistic Network for Science and Technology (HNST), 2018)
Globally, HIV infection (Human Immunodeficiency Virus) and AIDS (Acquired Immune Deficiency Syndrome) were still a problem in the health. East Java Province's case rate is in the top 10, which is 29.70%. The case rate number was still above the national figure of 26.85% until March 2016. Case Rate of East Java Province was in the 10th position but cumulatively the East Java Province is ranked first with 3,292 deaths until March 2016 compared to other provinces. Gresik Regency was include in the top 10 largest number of AIDS cases with 898 AIDS cases per 2017 increased compared to 2016. The aim of the study was to find out the factors related to mortality in HIV and AIDS patients in Ibnu sina gresik district general hospital. The research method was a restropective cohort with a total of 299 patients. Data analysis used cox non-proportional hazard with a value of α = 0.05. Based on the results of the analysis showed that medication adherence was p